Le chant funèbre en l’honneur d’Adonis – un epyllion ? - Antje Kolde (Aitia, 2016)
The paper investigates the literary genre of the Bion’s Ἀδώνιδος ἐπιτάφιος, the Epitaph for Adonis. A brief discussion of the text and of the two analyses devoted to its genre shows that the poet self-consciously blends traits of different genres in order to play with the reader’s expectations. If the poem clearly develops the reflection on literary genres begun by Hellenistic writers of the first generation, one may wonder whether it asks the question of the subject matter of literature, if literature may still have a subject matter of its own.